Characteristics of Shared Governance in Iranian Nursing Schools: Several Souls in One Body - Maryam Sattarzadeh-Pashabeig; Foroozan Atashzadeh-Shoorideh; Mohammad-Mehdi Sadoughi; Alice Khachian; Mansoureh Zagheri-tafreshi (Wolters Kluwer Medknow Publications, 2018)
Background: Shared governance is a decentralized structural model that gives individuals the right to make decisions and a position analogous to managers. The shared governance is different based on context in every organization. This study identified the characteristics of shared governance in Iranian nursing schools. Materials and Methods: In this qualitative research, 11 participants were selected using purposive sampling method. Deep semi-structured interviews were conducted, and the data were analyzed using conventional content analysis. Lincoln and Guba's criteria were used to verify the accuracy and trustworthiness of the data. Results: Through data analysis, the theme of "several souls in one body" was achieved in addition to the seven categories of "climates based on common interests," "conscious participatory decision-making," "mutual accountability," "multiplicity of ideas," "decentralized structure," "interrelationship," and "sublime organization." Conclusions: According to the findings, the characteristics of shared governance in the social culture of Iran are like several souls in one body, emphasizing all aspects of participation and morality in the organization. Managers and administrators in higher education and nursing faculties need to pay attention to all aspects of shared governance, including spirituality in managing the covered institutions.